2004
DOI: 10.3386/w10514
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Self-Control

Abstract: How significant are individual differences in self-control? Do these differences impact wealth accumulation? From where do they derive? Our survey-based measure of self-control provides insights into all three questions: 1.There are individual differences in self-control not only of a quantitative but also of a qualitative nature. In our sample, standard self-control problems of overconsumption are no more prevalent than are problems of under-consumption. 2.Standard selfcontrol problems do impede wealth accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 31 publications
3
28
0
Order By: Relevance
“…Amador, Werning, and Angeletos (2003) characterize optimal allocation rules when you put the two together. Ameriks, Caplin, Leahy, and Tyler (2004) quantify self-control with survey evidence and relate it to individual financial decisions. Benhabib and Bisin (2004) take a cognitive approach to a similar problem in which agents choose between automatic processes, which are subject to temptations, and control processes, which are not.…”
Section: Are Exotic Preferences "Behavioral"?mentioning
confidence: 99%
“…Amador, Werning, and Angeletos (2003) characterize optimal allocation rules when you put the two together. Ameriks, Caplin, Leahy, and Tyler (2004) quantify self-control with survey evidence and relate it to individual financial decisions. Benhabib and Bisin (2004) take a cognitive approach to a similar problem in which agents choose between automatic processes, which are subject to temptations, and control processes, which are not.…”
Section: Are Exotic Preferences "Behavioral"?mentioning
confidence: 99%
“…A motivation for the analysis in this paper is captured by Ameriks, Caplin, Leahy, and Tyler (2004) who suggest that ''the impact of self-control problems should vary according to the liquidity characteristics of the underlying assets. .…”
Section: Empirical Methodologymentioning
confidence: 99%
“…Individuals differ in self-control while they are more sensitive at under-consumption than over-consumption (Ameriks, et al 2007). Huffman & Bonn (2005) have shown that individuals tend to borrow rather than exhibit credit constraints.…”
Section: Traders' Psychologymentioning
confidence: 99%